Evidence for the triadic model of adolescent brain development: Cognitive load and task-relevance of emotion differentially affect adolescents and adults. (August 2017) - Mueller, Sven C.; Cromheeke, Sofie; Siugzdaite, Roma; Nicolas Boehler, C.
Highlights: Little is known how emotion interacts with cognitive control in adolescents. Adolescents and adults completed emotional working memory task during 3T fMRI. Cognitive load interacted with emotion in adults but not adolescents in dlPFC. Ventral striatum activity to happy faces was larger in adolescents relative to adults. Under task relevance amygdala activation was stronger to happy faces in adolescents. Abstract: In adults, cognitive control is supported by several brain regions including the limbic system and the dorsolateral prefrontal cortex (dlPFC) when processing emotional information. However, in adolescents, some theories hypothesize a neurobiological imbalance proposing heightened sensitivity to affective material in the amygdala and striatum within a cognitive control context. Yet, direct neurobiological evidence is scarce. Twenty-four adolescents (12–16) and 28 adults (25–35) completed an emotional n-back working memory task in response to happy, angry, and neutral faces during fMRI. Importantly, participants either paid attention to the emotion (task-relevant condition) or judged the gender (task-irrelevant condition). Behaviorally, for both groups, when happy faces were task-relevant, performance improved relative to when they were task-irrelevant, while performance decrements were seen for angry faces. In the dlPFC, angry faces elicited more activation in adults during low relative to high cognitive load (2-back vs. 0-back). By contrast, happy faces elicited more activation in the amygdala in adolescents when they were task-relevant. Happy faces also generally increased nucleus accumbens activity (regardless of relevance) in adolescents relative to adults. Together, the findings are consistent with neurobiological models of adolescent brain development and identify neurodevelopmental differences in cognitive control emotion interactions.